Investigation into temperature field of nano-zirconia ceramics precision grinding. (1st January 2011) - Li, C.H.; Hou, Y.L.; Liu, Z.R.; Ding, Y.C.
A heat transfer model for the precision grinding process on nano-zirconia ceramics has been investigated. Based on the analysis of the processing properties of nano-zirconia ceramic materials, a theoretical model for the temperature field in the grinding of nano-zirconia ceramics was established. The model was then simulated and analysed under different grinding conditions. The effect of temperature dependent thermal properties and heat flux profile on temperature distribution in the workpiece has also been investigated. Parametric studies were carried out to study the effect of different input parameters such as the depth of cut, work feed rate and grinding speed on temperature distribution in the contact zone and in the workpiece across the grinding width and along the direction of movement. The results showed that, as the grinding wheel cut into the workpiece, the workpiece temperature rose sharply, and then levelled-off, with a high temperature gradient on the surface of workpiece. As the grinding depth of cut increased, a local high temperature took place in the grinding contact zone.